The hidden danger of usury financing system : a case of Turkey - Kayadibi, Saim (2012)
This paper critically examines the Pool Finance Economic System (PFES). In general terms riba, defined as both “interest” and “usury”, is a way to make money without engaging in either risk or effort. Conventional banks offer loans to state institutions at exorbitant interest rates with the collected loans from other state institutions at cheap interest rates. Therefore, they augment their income without risk by lending an institution’s money to another sector of the same institution. This practice makes them even more powerful in a state’s economic and financial life, for it enables them to force the government and/or state’s hand on any issue that is important to them. As Thomas Jefferson claimed, conventional banks and banking institutions can become more dangerous and threatening than modern armed forces. Not much research has been done on how this financial system, is formulated, implemented, achieves success and its interest free-interest nature. The objective is to investigate how an institution can protect itself from the potentially tremendous danger that such a practice represents to institutions and states by implementing the unique PFES method as an interest-free loan tool. One expected result is the provision of a unique method to solve finance problems. This PFES will guide institutions on how to spread their available money among the system’s other institutions collaboratively, rather than using extra interest-based loans from conventional banks or interest-based institutions. Simply stated, it is a matter of managing one’s own money via interest-free loans in practical economic and financial matters. The significance of this paper is its uniqueness and provision of an alternative approach to solving finance problems for small organizations and the state’s financial and economic issues.